Assessing the Influence of High Population Growth Rate on Food Security in Nyamweru Subcounty Rubanda District. - Twinamasiko, Derrick (Kabale University, 2024)
This study assessed the influence of the high population growth rate on food security in the Nyamweru Sub-County Rubanda district. The objectives of the study were to examine the role of population growth rate towards food security, to examine challenges affecting population growth rate on food security, and to find out ways of how a high population growth rate promotes food insecurity in Nyamweru sub-county Rubanda district. A cross-sectional survey design was used. Self-administered questionnaires and interviews were used in data collection and data was analyzed using Excel, a computer software to generate descriptive statistics such as frequencies and percentages, and data was presented in tables and text. From the study findings, the role of the population growth rate towards food security in the Nyamweru sub-county Rubanda district promotes food production. encourages saving and investments, high population growth puts greater pressure on health and improves its quality, leads to a rapid increase in school-age population that calls for more investment in education, high population growth leads to an efficiency of developing countries and their political system and high population puts pressure on urban physical infrastructures leading to development, the study results also on challenges affecting population growth rate on food security in Nyamweru sub county Rubanda district, were inadequate capital for investment, shortage of enough land. poor infrastructure development, climatic changes, over-utilization of land, and political instability the study results also on how a high population growth rate promotes food security in the Nyanweru sub-county Rubanda district the findings were through the development of drought-resistant crops, investment in rural infrastructure, irrigation, improved storage facilities and investment in sustainable technologies. The study recommends that family planning programs should be designed to provide information, services, and modern means of fertility control to those who are interested, the study recommended that the government should use several methods to control high population growth such as one or two children per family policy, girl child education through giving them scholarships and the researcher recommended that there should be sensitization of people through mass media about the dangers of high population so that people can reduce on early marriages.